Reclaiming Traditional Religious Authority in the Contemporary Era - Yazid, Yasril; Ardiansyah, Ardiansyah; Kholmuminov, Feruz; Rafdeadi, Rafdeadi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Existing studies have highlighted that traditional religious authorities can survive and adapt to technological and communication developments. However, previous studies did not reveal whether the traditional religious authority could adapt independently or whether other actors helped strengthen their authority and popularity on social media. This article focuses on several questions about why traditional religious authorities engage with Muslim youth and how they repackage their clerics to suit the culture of urban Muslim youth. Based on virtual ethnographic work carried out from 2021 to 2022 and personal communication with one of the Muslim youth involved with traditional religious authorities on social media, this article shows that Ustaz Abdul Somad and Ustaz Hanan Attaki, who are part of traditional religious authorities, can adapt to technological developments thanks to the support of Muslims youth. The consequence of this support is that they adapt youth culture to repackage their ulama.